Electrolyte for potassium ion batteries and potassium ion batteries containing the same

KR103029973B1Active Publication Date: 2026-10-13국립순천대학교산학협력단 +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
KR1020240130501
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2026-10-13
Estimated Expiration
2044-09-26

Smart Images

  • Figure 112024105136433-PAT00015_ABST
    Figure 112024105136433-PAT00015_ABST
Patent Text Reader

Abstract

The present invention relates to an electrolyte for an aqueous potassium ion battery and an aqueous potassium ion battery containing the same. The electrolyte for a potassium ion battery according to the present invention comprises a cyano (C≡N) group and a trifluoromethanesulfonyl group.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to an electrolyte for an aqueous potassium ion battery and an aqueous potassium ion battery containing the same. Background Technology

[0003] Aqueous metal-ion batteries using aqueous electrolytes are being developed to be safer and lower manufacturing costs compared to non-aqueous metal-ion batteries. However, the narrow electrochemical stability window (ESW) of aqueous electrolytes and the resulting low energy density (ED) have been problematic. This issue has been resolved to some extent by applying high-concentration lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) to aqueous lithium-ion batteries. Currently, aqueous lithium-ion batteries can achieve an energy density of approximately 300 Wh / kg, which is about half that of non-aqueous lithium-ion batteries.

[0004] Research is being conducted to apply the partial success in the field of aqueous lithium-ion battery electrolytes to aqueous sodium-ion batteries or aqueous potassium-ion batteries, but an electrolyte for aqueous potassium-ion batteries with a wide electrochemical stability window and excellent low-temperature stability has not been developed. Prior art literature

[0006] Republic of Korea Published Patent Application No. 2024-0031084 The problem to be solved

[0007] The objective of the present invention is to provide an electrolyte for a potassium ion battery that provides a good electrochemical stability window and low-temperature stability suitable for application in aqueous potassium ion batteries, and a potassium ion battery containing the same.

[0008] However, the problems that the present invention aims to solve are not limited to those mentioned above, and other unmentioned problems will be clearly understood by those skilled in the art from the description below. means of solving the problem

[0010] A first aspect of the present invention for solving the above problem is to provide an electrolyte for a potassium ion battery comprising a potassium imide salt comprising a cyano (C≡N) group and a trifluoromethanesulfonyl group.

[0011] A second aspect of the present invention for solving the above problem is to provide a potassium ion battery comprising a positive electrode, a negative electrode disposed opposite to the positive electrode, a separator disposed between the positive electrode and the negative electrode, and an electrolyte for a potassium ion battery according to a first aspect disposed between the positive electrode and the negative electrode. Effects of the invention

[0013] The electrolyte for a potassium ion battery according to the present invention has an expanded electrochemical stability window and maintains a liquid state for a long period at low temperatures, which is advantageous for the design of potassium ion batteries.

[0014] In addition, the electrolyte for a potassium ion battery according to one embodiment of the present invention has excellent compatibility with previously developed electrode materials.

[0015] In addition, the electrolyte for a potassium-ion battery according to one embodiment of the present invention can achieve high voltage and stable low-temperature characteristics through combination with a specific electrode material.

[0016] However, the effects of the present invention are not limited to those mentioned above, and other unmentioned effects will be clearly understood by a person skilled in the art from the description below. Brief explanation of the drawing

[0018] Figure 1A shows the results of measuring the change in saturation concentration according to the mole fraction of a binary mixture of KTFSI / KDCA, Figure 1B shows the DSC curves of KDCA, KTFSI, and KCTFSI, and Figure 1C shows the results of comparing the solubility of Li, Na, and K salts using TFSI, CTFSI, and DCA anions. Figure 2A shows the conductivity and activation energy (Ea) according to the concentration of KCTFSI, Figure 2B shows the change in viscosity and density according to the concentration of KCTFSI, and (C) shows the Walden plot of KCTFSI. Figure 3A shows the DSC curve during cooling (blue line) and the DSC curve during subsequent heating between 60 and -87°C at 1°C / min (red line), Figure 3B shows the DSC curve during repeated heating and cooling, and Figure 3C shows photographs of 30m KFSI, 22m KOTF, and 32.2m KCTFSI after storage at -15°C. Figure 4 shows the LSV results at 0.2 mV / s for KTFSI (1.5 m), KCTFSI (5, 10, 20, and 32.2 m) solutions for stainless steel (SS) and 32.2 m KCTFSI for aluminum (Al). Figure 5 shows the elemental composition of the aluminum surface at various negative potentials. Figure 6 shows the LSV for aluminum in various KCTFSI (10, 20, 32.2 m) solutions. Figure 7 shows the CV curves of PTCDI and KFeHCF at 32.2 m KCTFSI at 0.2 mV / s. Figure 8 is a potential graph of Al in the PTCDI at various constant currents. Figure 9 is a potential graph of Al in KFeHCF at various constant currents. Figure 10 is the charge / discharge profile of the entire cell (PTCDI | KFeHCF) at various operating temperatures. Figure 11 shows the charging capacity (filled circles) and discharging capacity (open circles) of a whole cell (PTCDI | KFeHCF) of various C-rates at room temperature (RT). Figure 12 shows the charging capacity (filled circles) and discharging capacity (open circles) of a whole cell (PTCDI | KFeHCF) of various C-rates at -15℃. Figure 13 shows the capacity retention and Coulomb efficiency during 500 charge / discharge cycles at -15℃. Figure 14 is the CV curve at room temperature of 0.2 mV / s when KVPF is applied as the anode. Figure 15 is the charge / discharge profile of the entire cell (PTCDI | KVPF) at various temperatures. Figure 16 shows the capacity retention and Coulomb efficiency of the entire cell (PTCDI | KVPF) at -15℃. Figure 17 schematically shows the cross-sectional structure of a potassium ion battery. Specific details for implementing the invention

[0019] Embodiments of the present invention are described below with reference to the attached drawings so that those skilled in the art can easily implement them. However, the present invention may be embodied in various different forms and is not limited to the embodiments described herein.

[0020] In addition, to clearly explain the present invention in the drawings, parts unrelated to the explanation have been omitted, and similar parts throughout the specification have been given similar reference numerals.

[0021] Throughout this specification, when a part is described as "comprising" a certain component, this means that, unless specifically stated otherwise, it does not exclude other components but may include additional components.

[0022] Terms of degree used in this specification, such as “about,” “substantially,” etc., are used to mean at or near the stated value when inherent manufacturing and material tolerances are presented in the stated meaning, and are used to prevent unscrupulous infringers from unfairly exploiting the disclosure in which precise or absolute values ​​are mentioned to aid in understanding the invention.

[0024] [Electrolyte for Water-based Potassium Ion Batteries]

[0025] The electrolyte for an aqueous potassium ion battery according to the present invention is characterized by being an aqueous solution of a potassium imide salt containing a cyano (C≡N) group and a trifluoromethanesulfonyl group.

[0026] The potassium imide salt according to the present invention is characterized by having an asymmetric structure including cyano (C≡N) groups and trifluoromethanesulfonyl groups, thereby expanding the window of electrochemical stability compared to conventional electrolytes for potassium ion batteries and obtaining the characteristic of maintaining a liquid state for a long time at low temperatures.

[0027] The above potassium imide salt may be potassium cyano(trifluoromethanesulfonyl)imide (C2F3KN2O2S).

[0028] The electrolyte according to the present invention includes water (H2O) as a solvent, and the molar ratio of the potassium imide salt in the electrolyte may be in a high concentration state compared to the molar ratio of water (H2O).

[0029] In the case of general aqueous electrolytes, an aqueous solution (salt in water) in which a small amount of salt is dissolved in an excess amount of water is used, whereas the electrolyte according to the present invention is used in a state in which an excess amount of salt is dissolved in a small amount of water, thereby obtaining an effect different from that of a low-concentration aqueous solution.

[0030] In addition, the solvent may further include organic solvents other than water, such as ethers, carbonates, nitriles, alcohols, ketones, amines, amides, sulfur compounds, and hydrocarbons. In addition, the water in the solvent may be 50 mol% or more, 60 mol% or more, 70 mol% or more, 80 mol% or more, 90 mol% or more, 95 mol% or more, or 100 mol%.

[0031] In the electrolyte according to the present invention, the concentration of the potassium imide salt may be 25 m or more, preferably 30 m or more.

[0032] The saturated solubility of the above potassium imide salt may preferably be 30 m or more.

[0033] In the electrolyte according to the present invention, when the electrolyte is repeatedly cooled and heated between -30 and 60°C, an endothermic or exothermic reaction may not occur. That is, the electrolyte according to the present invention can be used over a wider temperature range compared to conventional electrolytes.

[0034] In the electrolyte according to the present invention, the electrochemical stability window (△E) of the electrolyte may be 2.5V or higher, 3.0V or higher, or 3.5V or higher.

[0036] [Water-based potassium ion battery]

[0037] Figure 17 schematically shows the cross-sectional structure of a potassium ion battery.

[0038] Referring to FIG. 17, a potassium ion battery (100) comprises a positive electrode (110), a negative electrode (120) positioned opposite the positive electrode (110), a separator (130) positioned between the positive electrode (110) and the negative electrode (120), and an electrolyte (140) injected between the positive electrode (110) and the negative electrode (120).

[0039] The positive electrode (110) may have a structure in which a positive active material layer (112) is coated on a positive current collector (111), for example. The positive current collector (111) may be made of various known shapes of materials that can be used as positive current collectors for aqueous potassium ion batteries, for example, it may be made of stainless steel or a metal including aluminum (Al). The positive active material may be used without limitation as long as it is a material containing a potassium element that can be used in an aqueous potassium ion battery, for example, it may include one or more selected from metal oxides containing potassium, Prussian blue (K2Fe4[Fe(CN)6]3), KVPO4F, and metal sulfides.

[0040] The above-mentioned negative electrode (120) may have a structure in which a negative active material layer (122) is coated on a negative current collector (121), for example. The above-mentioned negative current collector (121) may be made of a material that can be used as a negative current collector for a water-based potassium ion battery and may be made of various known shapes, for example, stainless steel or a metal including aluminum (Al). The above-mentioned negative active material (122) may be used without limitation as long as it is a negative active material that can be used for a water-based potassium ion battery, for example, may include one or more selected from perylene-3,4,9,10-tetracarboxylic acid diimide (PTCDI), metal complex oxide, metal sulfide, KTi2(PO4)3, and NASICON-type compounds.

[0041] The above separator (130) can be used without special limitations as long as it is made of a material that can be used in an aqueous potassium ion battery. Preferably, it may be a hydrophilic material.

[0043] <Experimental Example>

[0044] The materials used in the experiment were KCTFSI (Provisco), KTFSI (Merck), KOTF (Merck), KFSI (TCI chemical), and PTCDI (Alfa Aesar), and the materials sold by the companies listed in parentheses were used as they are, and the water-soluble electrolyte was prepared using high-purity deionized (DI) water at room temperature (RT).

[0045] For the synthesis of KFeHCF, first, 0.25 mmol of potassium hexacyanoferrate trihydrate (K4Fe(CN)6·3H2O) was added to a solution of 0.1 M HCl in 50 mL of ethylene glycol. The mixture was then stirred to obtain a clear solution, which was heated in an autoclave at 80°C for 24 hours. The resulting product was filtered, washed with deionized water and ethanol, and finally dried under a vacuum at 60°C to obtain pure KFeHCF nanocubes.

[0046] KVPO4F powder was synthesized through a two-step solid-state process. First, NH4H2PO4, V2O5, and acetylene black (greater than 10 wt%) were ball-milled with zirconia balls and acetone at 500 rpm for 12 hours, followed by drying. The mixture was then compressed into pellets and sintered at 750°C under an Ar flow for 5 hours to produce VPO4. Next, KF and VPO4 were mixed using a planetary ball mill at 500 rpm for 6 hours. The mixed powder was pelletized and sintered at 650°C under an Ar flow for 6 hours to obtain pure KVPO4F.

[0047] To study the electrochemical characteristics and half-cell performance of the KCTFSI electrolyte, a three-electrode cell setup consisting of Pt foil and Ag / AgCl was used as the counter electrode and reference electrode, respectively. The working electrode was stainless steel or aluminum foil with an area of ​​0.817 cm².

[0048] Coin cells (CR2032, Wellcos) were used for full cell testing. For the cathode composites of KFeHCF and KVPF, a slurry was prepared by mixing the active material, acetylene black, and polyvinylidene fluoride (PVdF) in a weight ratio of 8:1:1 and using N-methyl-2-pyrrolidone as the solvent. For the cathode electrode, a slurry was prepared using PTCDI (70 wt%), acetylene black (20 wt%), and PVdF (10 wt%). The prepared slurries were applied to an Al mesh, vacuum dried at 100°C for 12 hours, roll-pressed, and then punched to a predetermined size. Electrochemical tests were performed in an automatic WBCS 3000 cycler (WonAtech). Low-temperature measurements were performed in a temperature-controlled battery test chamber (DS-11F-BSP, Dasol Scientific Co., Korea).

[0050] KCTFSI Solubility

[0051] Figure 1A shows the results of measuring the change in saturation concentration according to the mole fraction of a binary mixture of KTFSI / KDCA, Figure 1B shows the DSC curves of KDCA, KTFSI, and KCTFSI, and Figure 1C shows the results of comparing the solubility of Li, Na, and K salts using TFSI, CTFSI, and DCA anions.

[0052] The solubility of a potassium imide salt solution containing a cyano (C≡N) group and a trifluoromethanesulfonyl group (TFSI) (hereinafter referred to as 'KCTFSI') and a mixed salt solution of potassium imide salt containing a trifluoromethanesulfonyl group (TFSI) (hereinafter referred to as 'KTFSI'), which is a symmetric imide salt with similar chemical composition, and potassium dicyanamide (hereinafter referred to as 'KDCA') was compared.

[0053] Generally, it is known that the solubility of mixed anion solutions is higher than the saturation concentration of individual salts; however, as shown in Figure 1A, the solubility curve of the KTFSI-KDCA binary salt showed lower solubility than KDCA (9.2 m) and KTFSI (1.5 m) across the entire composition range, exhibiting behavior contrary to what is known. This behavior is presumed to be related to the high cosmotropic / chaotropic properties of the KDCA-TFSI anion.

[0054] In addition, as shown in Figure 1B, the results of DSC analysis showed that while the melting point of KDCA was approximately 222°C and the melting point of KTFSI was approximately 194°C, the melting point of KCTFSI was approximately 133°C, which is significantly lower than these, indicating a high potential for using KCTFSI as an aqueous salt electrolyte.

[0055] In addition, as shown in Fig. 1C, the solubility is significantly higher than that of KTFSI and KDCA. While the solubility of KTFSI is approximately 1.5 m and that of KDCA is approximately 9.2 m, the solubility of KCTFSI is 32.2 m. This high solubility of KCTFSI enables the realization of an ultra-high concentration electrolyte (water in salt), thereby expanding the electrochemical stability window.

[0057] Conductivity of KCTFSI solution

[0058] Figure 2A shows the conductivity and activation energy (Ea) according to the concentration of KCTFSI, Figure 2B shows the change in viscosity and density according to the concentration of KCTFSI, and (C) shows the Walden plot of KCTFSI.

[0059] As shown in Fig. 2A, the conductivity of the KCTFSI solution exhibited a convex peak as a function of concentration. The presence of this conductivity peak signifies a transition from a 'salt in water' state to a 'water in salt' state. The conductivity was maximum at a concentration of 5 m of KCTFSI solution and subsequently showed a tendency to gradually decrease as the concentration increased up to the saturation concentration. However, the conductivity of the saturation concentration of 32.2 m KCTFSI solution was 28 mS·cm. -1 Approximately 10 mS·cm of commercial non-aqueous electrolytes -1 It was maintained at a higher level. In addition, consistent with the change in conductivity, a minimum value was observed when the concentration of the KCTFSI solution was 5 m. This change is attributed to a change in the ion transport mechanism.

[0060] As shown in Figure 2B, the viscosity and density of the saturated 32.2m KCTFSI were significantly higher than those of the low-concentration solution, which implies that the high conductivity of 32.2m KCTFSI may be related to ion movement separated from viscosity.

[0061] As shown in Fig. 2C, the Walden plot also shows the fluidity (η) as the KCTFSI concentration increases. -1 The ratio of molar conductivity (Λ) to ) approaches the ideal KCl line, indicating that the 32.2m KCTFSI solution has high ionic conductivity.

[0063] Temperature characteristics of KCTFSI solution

[0064] Figure 3A shows the DSC curve during cooling (blue line) and the DSC curve during subsequent heating between 60 and -87°C at 1°C / min (red line); Figure 3B shows the DSC curve during repeated heating and cooling between -30 and 60°C; and Figure 3C shows photographs of 30m KFSI, 22m KOTF, and 32.2m KCTFSI after storage at -15°C.

[0065] For the application of high-concentration salt electrolytes, it is important to prevent crystallization that occurs when the battery operates at low temperatures for an extended period.

[0066] Accordingly, as shown in Fig. 3A, the thermal behavior of a 32.2 m KCTFSI solution was monitored by cooling and heating it within the range of 60 to -87°C. Although there was no exothermic peak up to -50°C during cooling, a distinct exothermic process associated with the partial crystallization of water (H2O) or KCTFSI hydrate appeared during subsequent cooling, along with the formation of a glassy state.

[0067] During subsequent heating, a low-temperature crystallization process began at approximately -44°C, a multiple melting process proceeded at approximately -15°C, and a liquid phase transition occurred at 3°C. In particular, the liquidus temperature is one of the lowest temperatures among known ultra-high concentration alkali-ion aqueous electrolytes.

[0068] In addition, as shown in Fig. 3B, when the 32.2m KCTFSI was repeatedly cycled between -30 and 60°C, no thermal event occurred (the endothermic peak at approximately -30°C in Fig. 3B is due to instrument instability at the beginning of the measurement), which means that a supercooled state is maintained at low temperatures.

[0069] In addition, as shown in Fig. 3C, after storage at -15℃, 30m KFSI and 22m KOTF solidified immediately at -15℃, but no precipitation was observed in the 32.2m KCTFSI solution for one month.

[0070] From the experimental results above, it can be seen that the 32.2m KCTFSI solution is an electrolyte that can be used over a wider temperature range compared to conventional solutions.

[0072] Electrochemical properties of KCTFSI solution

[0073] Figure 4 shows the LSV results at 0.2 mV / s for KTFSI (1.5 m), KCTFSI (5, 10, 20, and 32.2 m) solutions for stainless steel and 32.2 m KCTFSI for aluminum, Figure 5 shows the elemental composition of the aluminum surface at various negative potentials, and Figure 6 shows the LSV for aluminum in various KCTFSI (10, 20, and 32.2 m) solutions.

[0074] To determine the effect of concentration on the electrochemical stability window (△E), linear sweep voltammetry (LSV) of aqueous solutions at various KCTFSI concentrations was compared. During a potential scan of the open-circuit potential (OCP) versus the Ag / AgCl reference electrode, the current passing through the stainless steel (SS) working electrode was recorded at a rate of 0.1 mV / s. At this time, platinum (Pt) foil was used as the counter electrode.

[0075] As shown in FIG. 4, the cathode and anode limits (E Ia and E Ic , determined by current levels smaller than ±10 uA / ㎠) was found to increase simultaneously with the increase in KCTFSI concentration. E la It shifted in the positive direction from 1.11 V (5 m KTFSI) to 1.35 V (32.2 m KTFSI). Additionally, Elc decreased from -0.87 V (1.5 m KTFSI) to -1.17 V (32.2 m KCTFSI), creating an electrochemical stability window (△E) of 2.52 V in stainless steel. It can be seen that the △E at 32.2 m KCTFSI is wider than the △E of 1.81 V in the saturated KTFSI solution.

[0076] In addition, if the entire current collector is changed from stainless steel to aluminum, the △E of the 32.2m KCTFSI solution can be further expanded to 3.80V, which is, E in Al lc is lowered to -1.59V, and E la It is also due to the significant increase to 2.21V.

[0077] In addition, as shown in Fig. 5, it can be seen that a Solid Electrolyte Interphase (SEI) layer is formed from the surface composition of the Al electrode subjected to various negative potentials.

[0078] In addition, as shown in Fig. 6, the current level of Al in 10m and 20m KCTFSI solutions is higher than that of stainless steel, which indicates that E is used only in high-concentration solutions with insufficient water, rather than in solutions with abundant water. la This implies that expansion is possible. In addition, the image of the Al surface shows that while corrosion occurred in the 10m and 20m KCTFSI solutions, the Al surface did not corrode in the 32.2m KCTFSI solution. In other words, when using Al as a current collector, a KCTFSI solution of 25m or more is preferable, and a KCTFSI solution of 30m or more is even more preferable.

[0080] Charge / Discharge Characteristics of Potassium-Ion Batteries with KCTFSI Solution

[0081] Figure 7 shows the CV curves of PTCDI and KFeHCF in 32.2 m KCTFSI at 0.2 mV / s, Figure 8 shows the potentialogram of PTCDI for Al at various constant currents, and Figure 9 shows the potentialogram of KFeHCF for Al at various constant currents.

[0082] The compatibility of KCTFSI with electrode materials was evaluated. Perylene-3,4,9,10-tetracarboxylic acid diimide (hereinafter referred to as 'PTCDI') was selected as the negative electrode, considering its proven stability as an electrode material in aqueous potassium-ion batteries.

[0083] As shown in Figure 7, the cyclic voltammetry (CV) of PTCDI for Al in a 32.2 m KCTFSI solution exhibited a two-step redox process accompanied by potassiumation / depotassiumation. No significant distortion in the current response was observed when cycled down to -1.30 V versus Ag / AgCl.

[0084] As shown in Fig. 8, consistent with the half-wave potential of the CV curve, the potentiogram of PTCDI at various current densities between -1.30 V and 0.20 V exhibited two potential plateaus at approximately -0.96 V and -0.14 V. Furthermore, the redox activity of PTCDI was stable during repeated cycling (116 mAh / g -> 110 mAh / g for 200 cycles at 2C, fading rate = 0.03 mAh / g per cycle; see insert in Fig. 8A). This stable capacity retention rate demonstrates that a 32.2 m KCTFSI solution can be applied to PTCDI.

[0085] Next, the compatibility of a 32.2 m KCTFSI solution with a Prussian blue (K2Fe[Fe(CN)6]·2H2O, hereinafter referred to as 'KFeHCF') cathode was evaluated. Pure KFeHCF with a nanocube shape was synthesized via a hydrothermal method. The potentiogram of KFeHCF with respect to Al showed a two-stage potassiumization / depotassium process with plateau potentials at 0.32 V and 0.97 V (Fig. 8B), consistent with the CV results in Fig. 7. In addition, a reasonable capacity retention rate was confirmed over 200 cycles with a degradation rate of 0.03 mAh / g per cycle.

[0086] Next, the entire cell (PTCDI (3.5 mg) | 32.2 mg KCTFSI | KFeHCF (3.8 mg)) was assembled and its electrochemical properties were investigated under various conditions.

[0087] Figure 9 compares the charge / discharge profile at room temperature (RT) with the charge / discharge profile at low temperatures (0°C and -15°C). As can be seen in Figure 9, the shape and capacity of the charge / discharge profile at 0°C and -15°C were similar to the profile shape at room temperature. Although the discharge capacity decreased as the temperature decreased due to the slow diffusion of potassium ions in the high-concentration electrolyte or solid electrode, it showed a significant level of 106 mAh / g and 85 mAh / g (at 0°C and -15°C, respectively) compared to the capacity delivered at room temperature (115 mAh / g).

[0088] In addition, as confirmed in Fig. 10, thanks to the superionicity of 32.2 m KCTFSI and the excellent rate performance of the electrode material, the PTCDI || KFeHCF whole cell exhibited excellent capacity retention at high C-rates. Although the capacity gradually decreased as the C-rate increased at room temperature due to the continuous increase in overpotential, the capacity at 20 C reached about 66% of the value at 1 C.

[0089] Meanwhile, as confirmed in Fig. 11, regarding the capacity decrease according to the C-rate at -15°C, the capacity was only 20 mAh / g at 20°C, but relatively high capacities of 90 mAh / g and 81 mAh / g were delivered at 0.5°C and 1°C, respectively. From this, it can be concluded that while high-rate operation such as at 20°C may be difficult at low temperatures, excellent stability was demonstrated at intermediate C-rates. As confirmed in Fig. 12, when cycling under conditions of -15°C and 1°C, the initial capacity of approximately 81 mAh / g decreased slowly and maintained 88% at 71 mAh / g after 500 cycles. In other words, no rapid decrease in capacity was observed, which reflects the supercooling characteristics of the 32.2 m KCTFSI high-concentration solution. To visually verify this, the cell after 500 cycles was frozen in ice at -16°C, and the operation of the LED display (7.5 mW) was observed (inset). Observations showed that the light was maintained for about 20 minutes, which corresponds to the discharge energy of approximately two coin cells (2.82V × 140 mAh / g positive × 7.6 mg negative = 3.0 mWh).

[0090] High E of KCTFSI for Al laTo utilize this, KVPO4F (hereinafter referred to as 'KVPF') was selected as the cathode, and its compatibility with KCTFSI was evaluated. As confirmed in Figure 13, the redox behavior of KVPF occurs between 0.9V and 1.8V versus Ag / AgCl, exhibiting two distinct redox peaks approximately 0.7V higher than those of KFeHCF. In a 32.2m KCTFSI solution, the CV curve of KVPF shows oxidation starting at 1.0V versus Ag / AgCl with a sustained high current level up to 1.8V without two sharp peaks, unlike what is observed in conventional carbonate-based organic electrolytes. In particular, the high cutoff potential of 1.8V corresponds to 4.9V versus K / K+, which implies that a high-concentration KCTFSI solution is suitable for the field of high-pressure aqueous potassium-ion batteries.

[0091] The galvanostic charge / discharge profile also exhibited redox behavior within a similar potential range (Fig. 14). The potential steadily increased and decreased between 1.0 V and 1.8 V during charge / discharge at room temperature. Although no identifiable plateau region was present, the reversible capacity at 1 C reached 80% of the theoretical capacity of the KVPF (104 mAh / g versus 131 mAh / g), indicating the applicability of the KVPF in a 32.2 m KCTFSI solution at room temperature. Meanwhile, at lower operating temperatures, the capacity decreased slightly with increasing overpotential, but the discharge capacity at -15°C reached approximately 86 mAh / g.

[0092] Finally, to utilize the high voltage characteristics of the KVPF, an entire cell was fabricated with the KVPF integrated as the anode.

[0093] Figure 15 compares the charge / discharge profiles of the entire cell (PTCDI (3.5 mg) | 32.2 m KCTFS | KVPF (3.0 mg)) at various temperatures. As the operating temperature decreases, the capacity continuously decreases. The discharge capacity of 126 mAh / g at 50°C decreased stepwise to 110 mAh / g, 91 mAh / g, and 80 mAh / g as the temperature decreased to room temperature, 0°C, and -15°C, respectively, but it can be seen that a certain level of discharge capacity can be achieved even at low temperatures.

[0094] In addition, the application of KVPF resulted in high-voltage charge / discharge behavior. As confirmed in Fig. 16, the entire cell exhibited adequate stability during charge / discharge cycles at -15℃.

[0095] The high voltage and low temperature characteristics of the entire cell (PTCDI (3.5 mg) | 32.2 m KCTFS | KVPF (3.0 mg)) as described above are unique performance characteristics not known in aqueous potassium-ion batteries. Explanation of the symbols

[0097] 100: Potassium-ion battery 110: Anode 111: Positive current collector 112: Positive active material layer 120: Cathode 121: Cathode current collector 122: Cathode active material layer 130: Separator 140: Electrolyte

Claims

Claim 1 An electrolyte for a potassium-ion battery comprising a potassium imide salt containing cyano (C≡N) groups and trifluoromethanesulfonyl groups, and water as a solvent, wherein the concentration of the potassium imide salt is 25 m or more. Claim 2 In claim 1, the potassium imide salt comprises potassium cyano(trifluoromethanesulfonyl)imide (C2F3KN2O2S), an electrolyte for a potassium-ion battery. Claim 3 delete Claim 4 delete Claim 5 An electrolyte for a potassium ion battery according to claim 1 or 2, wherein the saturated solubility of the potassium imide salt is 30 m or more. Claim 6 An electrolyte for a potassium-ion battery according to claim 1 or 2, wherein the electrolyte does not exhibit an endothermic or exothermic reaction when repeatedly cooled and heated between -30 and 60°C. Claim 7 An electrolyte for a potassium-ion battery according to claim 1 or 2, wherein the electrochemical stability window (△E) of the electrolyte is 2.5V or higher. Claim 8 A potassium ion battery comprising a positive electrode, a negative electrode disposed opposite to the positive electrode, a separator disposed between the positive electrode and the negative electrode, and an electrolyte for a potassium ion battery according to claim 1 or 2 disposed between the positive electrode and the negative electrode. Claim 9 In claim 8, the negative electrode comprises a negative current collector and a negative active material layer coated on the negative current collector, and the negative active material layer comprises perylene-3,4,9,10-tetracarboxylic acid diimide (PTCDI), a potassium ion battery. Claim 10 In claim 8, the positive electrode comprises a positive current collector and a positive active material layer coated on the positive current collector, and the positive active material layer comprises Prussian blue (K2Fe[Fe(CN)6]) or KVPO4F, a potassium ion battery.

Citation Information

Patent Citations

  • Aqueous secondary battery

    KR1020210103749A

  • Aqueous rechargeable battery including organic positive active material

    KR1020230063660A

  • Aqueous potassium ion battery

    KR1020240031084A